Three-body correlations in nonlinear response of correlated quantum liquid - Tokuro Hata (Nature Portfolio, 2021)
Recent theory has shown that the non-equilibrium response of a Kondo model can be described by the Fermi liquid theory with three-body correlations. Here, the authors experimentally measure such correlations in the nonlinear conductance of a Kondo-correlated quantum dot.